Association of Antibodies to Prevotella copri in Anti–Cyclic Citrullinated Peptide‐Positive Individuals At Risk of Developing Rheumatoid Arthritis and in Patients With Early or Established Rheumatoid Arthritis. Issue 4 (22nd February 2023) - Seifert, Jennifer A.; Bemis, Elizabeth A.; Ramsden, Kristina; Lowell, Cassidy; Polinski, Kristen; Feser, Marie; Fleischer, Chelsie; Demoruelle, M. Kristen; Buckner, Jane; Gregersen, Peter K.; Keating, Richard M.; Mikuls, Ted R.; et al.
Abstract : Objective: Prevotella copri ( P copri ), a gut commensal, has been reported to be an immune‐relevant organism in individuals with rheumatoid arthritis (RA). This study sought to evaluate anti– P copri (anti– Pc ) antibody responses in our participant cohorts and to determine when in the natural history of RA such responses develop. Methods: We analyzed serum levels of immunoglobulin A (IgA) and IgG antibodies from a 27‐kd protein of P copri (anti– Pc ‐ p27), an immunogenic P copri protein, in study participants at risk of developing RA, participants who transitioned to RA, participants with early RA (<1 year of disease), and participants with established RA, with comparisons made to their matched controls. We also evaluated anti– Pc ‐p27 antibody levels in individuals stratified by RA‐related autoantibody status. Results: Overall, participants with RA had significantly higher IgA anti– Pc ‐p27 antibody levels and trended toward higher IgG anti– Pc ‐p27 antibody levels compared with matched controls. When stratified by early versus established RA, participants with early RA had median IgG anti– Pc ‐p27 antibody levels that were overall higher, whereas median IgA anti– Pc ‐p27 antibody levels were statistically significantly higher in participants with established RA compared with their matched controls. In the autoantibody‐specific analyses, the at‐risk population with anti–cyclic citrullinated peptide (anti‐CCP) antibodies, but not rheumatoid factor (RF), trended toward increased levels of IgG anti– Pc ‐p27. Additionally, RA participants who were seropositive for both CCP and RF had significantly increased levels of IgA anti– Pc ‐p27 antibodies and trended toward higher levels of IgG anti– Pc ‐p27 antibodies compared with matched controls. Conclusion: Our findings support a potential etiologic role for P copri in both RA preclinical evolution and the subsequent pathogenesis of synovitis.